Cardiopulmonary exercise test: A 20-year (2002-2021) bibliometric analysis - Song, Lei; Qu, Hua; Luo, Jinwen; Wang, Wenting; Zheng, Liying; Xue, Mei; Shi, Dazhuo (Frontiers in Cardiovascular Medicine, 2022)
Background The clinical application value of cardiopulmonary exercise test (CPET) has increasingly attracted attention, and related research has been increasing yearly. However, there is no summary analysis of the existing CPET literature. This is the first bibliometric analysis of publications in the CPET. Methods CPET-related articles published between 2002 and 2021 were retrieved from the Web of Science Core Collection database. The search was limited to Articles and Reviews in English. CiteSpace software was used to conduct collaborative network analysis of countries/regions, institutions, authors, the co-occurrence of subject categories and keywords, and co-citation analysis of authors, journals, and references. Results A total of 4,426 publications were identified. During the study period, the number of published articles increased yearly. Developed countries from the Americas and Europe led the field. The University of Milan was the most prolific institution, with Ross Arena and Wasserman K being the most prolific and co-cited authors in the field, respectively. Cardiovascular System & Cardiology and Respiratory System were the main areas involved. Moreover, heart failure, oxygen uptake, and prognostic value were the central themes. Conclusions CPET had attracted widespread attention, and the number of publications will increase substantially according to the current growth trends. In the future, CPET is expected to be further adopted in large-scale clinical studies as a means of assessing the functional ability of patients to verify the efficacy of related interventions. High-quality evidence-based medical CPET-related indicators is expected to be used in clinical diseases risk prediction.